KUALITAS HIDUP LANSIA DI DUSUN GLONGGONGAN DESA SUMBER TEBU KECAMATAN BANGSAL MOJOKERTO - KARTININGRUM, EKA DIAH (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2017)
Elderly people face weaknesses, limitations and disabilities, so the quality of life of the elderly decreased. The purpose of this study was to identify the quality of life of the elderly. The design of this study is descriptive. The elderly population aged > 60 years old in Glonggongan Sumber Tebu Bangsal Mojokerto. The study sample is elderly> 60 years old as many as 31 elderly. The sampling technique used is simple random sampling for 3 months. The time of the research was conducted on 7 June to 7 August 2017. The technique of collecting data using questioner with interview technique using WHOQOL BRIEF. The results showed that more than half the elderly have a good quality of life and almost half have poor quality. Elderly with good quality of life can still do the activity though not all of them. Elderly men have poor quality of life, because of the many problems experienced such as mobility impairment.Keyword: quality, life, elderly